Performance Analysis Of Smooth Variable Structure Filter (SVSF) For Noise Reduction In Voltage, Current, And Power Estimation Of Photovoltaic (PV) Systems - Elly Hastiningtyas; Ike Yuni Wulandari; Heru Suwoyo (Universitas Medan Area, 2026)
Photovoltaic (PV) systems are renewable energy sources whose performance is affected by changes in irradiation and temperature, so that noise interference in voltage and current signals can degrade the quality of power processing. This study proposes the use of a Smooth Variable Structure Filter (SVSF) as a signal processing stage before being used by the MPPT algorithm, because SVSF has robust properties against model uncertainty and measurement interference. Testing was carried out through Matlab-based simulations with input voltage and current signals and Gaussian noise injection to represent dynamic PV operating conditions. The simulation results showed that the SVSF was able to reduce power fluctuations by 83.92%, with an MAE value of 3.06 W and an RMSE of 4.3 W. Thus, the proposed method is able to produce a filtered power signal that is smoother, has lower ripple, and is closer to the actual PV power characteristics